Numerical modelling of Tropical Cyclone Dineo and its rainfall impacts over north-eastern South Africa - Meyiwa, Sbongile (Department of Oceanography, 2020)
Widespread flooding over parts of Mozambique, Zimbabwe, Malawi, Botswana as well as north-eastern South Africa was experienced in February 2017. The flooding was associated with Tropical Cyclone Dineo that was generated in the Mozambique Channel on 12 February 2017 and made landfall over the south-central coast of Mozambique on 15 February. This study investigates the atmospheric circulation and potential mechanisms responsible for the heavy rainfall that occurred during the passage of ex-Tropical Cyclone Dineo inland from the Mozambican coast with focus on the rainfall patterns over north-eastern South Africa. Output from the Weather Research and Forecasting (WRF) model, the Climate Forecast System Reanalyses version 2 (CFSv2) atmospheric reanalysis, satellite derived rainfall and wind data, and station rainfall data are used for this purpose. Tropical Rainfall Measuring Mission (TRMM) rainfall estimates, WRF model rainfall and rainfall station data indicated that many parts of north-eastern South Africa experienced large amounts of rainfall during the final stages of Dineo (16-17 February 2017) while Mozambique experienced heavy rainfall soon after the cyclone made landfall. An inland trough ahead of Dineo led to substantial rainfall at this time over Malawi and Botswana. Furthermore, analysis of the station data revealed that in north-eastern South Africa some stations recorded about 80 % of their total monthly rainfall from this event. The WRF model run indicated low level monsoonal north-easterly moisture fluxes feeding into Dineo in the Mozambique Channel. Subsequent convergence over south-eastern Africa between this flow and the south-easterly cyclonic flux associated with Dineo led to substantial rainfall over Mozambique, Zimbabwe, Botswana and north-eastern South Africa. Although the 2016/17 tropical cyclone season recorded below average numbers of storms, it is suggested that the conditions prior to the storm iv formation were favourable for the track of Tropical Cyclone Dineo and landfall on the southcentral Mozambican coast.